Features of the mechanism of formation of the exchange rate - Niyazbekova, Sh.U.; Bunevich , K.G. (BUKETOV BUSINESS REVIEW, 2019)
In modern terms the exchange rate, being in a close relationship with the main macroeconomic indicators and reflecting the impact of external factors both on the economy, on the currency trading and on the psychology of market participants, plays a large role in the formation of the external economic and political relations. Exchange rate is usually defined by a currency and is determined through a process of matching currency on the monetary market through a system of supply and demand. This degree affects the international activities of the country, the movement of capital, the status of the currency and reproduction activity itself. In the study the exchange rate formation mechanism is analyzed, the influence of market participants on its formation is studied; the main causes of fluctuations of exchange rate are identified; methods and tools for exchange rate management are studied. The movement of exchange rates has a large-scale impact on the internal and external economy of the country of the world. Excess of funds lead to inflation in order to reduce it, in is necessary to raise the rate. The FRS rate affects the economy of the Russian Federation, raising of the accounting rate puts pressure on the currencies of other countries and on the Russian ruble (hereinafter — RUB).